INOVASI KEPALA SEKOLAH: STRATEGI PENINGKATAN PRESTASI AKADEMIK SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI - Tiara Alvionita, Della; Tuti Indriyani; Fransisko Chaniago (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study focuses on examining the innovations implemented by the principal in efforts to improve students’ academic achievement at State Junior High School 4, Paal Merah District, Jambi City. The purpose of this study is to identify the condition of students’ academic achievement and to describe the principal’s innovations in enhancing students’ academic performance. This research employs a descriptive approach combined with a qualitative method, utilizing observation, interviews, and documentation as data collection techniques. Data analysis involves data reduction, data presentation, and conclusion drawing. The findings indicate that students’ academic achievement at State Junior High School 4 Jambi City is generally categorized as fairly good, although in recent years there has been a tendency for a decline in the average report card scores. Nevertheless, the school continues to demonstrate academic achievements through students’ participation and accomplishments in various academic activities and competitions. The principal has implemented several academic innovations, including improving teachers’ competencies through training and workshops, providing motivation and appreciation to students, optimizing the use of learning facilities and infrastructure, and strengthening parental involvement in supporting students’ learning activities. The implementation of these innovations has had a positive impact on improving the learning process and gradually supporting the enhancement of students’ academic achievement.